Exploring the role of irisin as a potential biomarker in adolescents and young adults with polycystic ovarian syndrome - Sadaf Majeed; Hira Moin; Riffat Shafi; Sampana Fatima; Tatheer Zahra; Sarim Zafar (Women's Health)
Background: Irisin is a myokine potentially linked to insulin sensitivity. Polycystic ovarian syndrome (PCOS) is a prevalent hormonal condition defined by insulin resistance. Previous studies have reported elevated circulating irisin levels in adult females with PCOS. Objective: To examine the differences in serum irisin levels between lean and obese adolescents and young adults with PCOS and their respective lean and obese controls and to explore the relationship between irisin levels and the metabolic and reproductive characteristics of the participants. Design: Cross-sectional study design. Methods: The study included 60 cases of PCOS and 60 controls. These participants were categorized based on their body mass index (BMI) into lean and obese. Fasting serum irisin levels, physical, metabolic, hormonal, and reproductive characteristics of the participants were measured. Results: Lean cases of PCOS had significantly elevated levels of fasting serum irisin (PCOS = 17.07 ± 5.61 ng/ml vs lean controls = 11.04 ± 7.51 ng/ml; p  = 0.002), glucose, insulin, homeostasis model of assessment-insulin resistance index (HOMA-IR), luteinizing hormone (LH), estradiol, and testosterone and significantly lower levels of quantitative insulin sensitivity check index (QUICKI) compared to the lean controls. Obese cases of PCOS had significantly higher levels of fasting serum irisin (PCOS = 22.06 ± 3.83 ng/ml vs obese controls = 16.86 ± 6.74 ng/ml; p  = 0.011), glucose, insulin, HOMA-IR, LH, estradiol, and testosterone and significantly lower levels of follicle-stimulating hormone (FSH) and QUICKI compared to obese controls. The findings revealed a significant positive correlation of serum irisin levels with BMI, glucose, insulin, HOMA-IR, LH, estradiol, and testosterone(all p -values < 0.001). There was also a significant positive correlation with triglycerides (TAGs) ( p  = 0.001), total cholesterol ( p  = 0.005), and low-density lipoprotein cholesterol ( p  = 0.024). Additionally, there was a significant negative correlation with high-density lipoprotein cholesterol ( p  = 0.001) and QUICKI ( p  < 0.001) in the entire study cohort. Fasting serum glucose (β = 0.337, p  = 0.029), TAGs (β = 0.249, p  = 0.006), and LH (β = 0.382, p  = 0.004) were positive predictors of serum irisin concentrations in the overall sample. Conclusion: Lean and obese adolescent and young adult cases of PCOS had significantly higher fasting serum irisin levels than their respective controls. Metabolic and reproductive traits of the participants also correlated with irisin.